A method for preparing laser-induced composite micro-nanostructured graphene antibacterial surface
Through the preparation method of laser-induced composite micro-nano structure graphene, the problem of poor antibacterial effect of existing graphene surface materials is solved, and efficient broad-spectrum antibacterial properties and superhydrophobic properties are achieved, and it has wide application potential on antibacterial and antiviral surfaces.
Patent Information
- Application Number
- CN202411955908.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-28
- Publication Date
- 2025-04-04
AI Technical Summary
The existing complex preparation process limits the further application of graphene surface materials, especially in antibacterial and antiviral effects.
The preparation method of laser-induced composite micro-nano structure graphene was used to prepare graphene surfaces with superhydrophobicity and high-efficiency antibacterial properties by combining the CO2 laser engraving machine and the Nd:YAG laser marking machine.
The superhydrophobicity of composite micro-nano structure graphene was achieved, with a static hydrophobic angle of 150°, and a 96% antibacterial rate against Gram-positive Staphylococcus aureus, which is higher than that of the same type of antibacterial surface materials.
Smart Images

Figure CN119750561A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of graphene surface materials, and in particular to a method for preparing a laser-induced composite micro-nanostructured graphene antibacterial surface. Background Art
[0002] Microorganisms such as bacteria, fungi and viruses in nature can survive or accumulate on the surface of objects, causing indirect transmission and endangering human health. In some environments suitable for the growth of microorganisms, the surface of objects can become a "hotbed" for bacterial growth. Therefore, preventing and controlling surface pollution is an important means to prevent the spread of bacteria. Graphene is a new type of material with a nanoscale structure that has the characteristics of high electrical conductivity, thermal conductivity, specific surface area and easy functionalization. In recent years, researchers have discovered the excellent antibacterial and antiviral properties of graphene materials. The antibacterial and antiviral mechanisms of graphene-based materials are related to surface bacterial and viral inactivation, electrostatic capture, and physical and chemical destruction. These effects can be enhanced by functionalizing or enhancing the interaction between graphene and microbial particles.
[0003] The easily changeable surface morphology and surface properties of graphene materials are conducive to bacterial adsorption, thereby achieving effective killing effects, and are ideal materials for preventing bacterial contamination. The micro-nanostructured graphene surface can achieve the effect of regulating the attachment direction of microorganisms; the hydrophobic surface can have a strong van der Waals interaction with the phospholipids of bacterial and viral membranes, resulting in the destruction of the cell membrane structure. In addition, graphene also has an electrothermal effect, which can enhance the ability of airborne suicide viruses. Therefore, micro-nanostructured graphene surface materials have great potential in the new generation of sustainable materials. However, the existing complex preparation process limits the further application of graphene surface materials. Summary of the invention
[0004] In view of this, the purpose of the present application is to provide a method for preparing a laser-induced composite micro-nanostructured graphene antibacterial surface. The obtained composite micro-nanostructured graphene has super hydrophobicity, and its static hydrophobic angle reaches 150°, and at the same time exhibits efficient broad-spectrum antibacterial properties. Among them, for Gram-positive Staphylococcus aureus, the antibacterial rate of the composite micro-nanostructured graphene reaches 96%, which is higher than the same type of antibacterial surface materials. In addition, since the method has the advantages of high efficiency and large-area preparation, laser-induced graphene can be widely used in antibacterial and antiviral surfaces.
[0005] The present application provides a method for preparing a laser-induced composite micro-nanostructured graphene antibacterial surface, comprising:
[0006] Using a CO2 laser engraving machine, the polyimide film is graphitized using the local high temperature generated by the laser to prepare three-dimensional porous graphene with stable surface properties;
[0007] The prepared three-dimensional porous graphene was rotated 90°;
[0008] Using a Nd:YAG laser marking machine, a pulsed laser is used to scan the surface of the rotated three-dimensional porous graphene line by line in the vertical direction to prepare composite micro-nanostructured graphene.
[0009] Furthermore, before using the CO2 laser engraving machine for graphitization, the method further includes:
[0010] The polyimide film was ultrasonically cleaned using anhydrous ethanol to remove surface dirt;
[0011] The polyimide film after ultrasonic cleaning was dried in a vacuum oven at 60° C. to allow the polyimide film to completely adhere to the glass slide.
[0012] Furthermore, the thickness of the polyimide film is 125 μm.
[0013] Furthermore, the working parameters of the Nd:YAG laser marking machine are set as follows:
[0014] The excitation wavelength is 1064 nm, the excitation frequency is 20 KHz, the laser power is 1 W, the scanning speed is 200 mm / s, and the scanning interval is 50 μm.
[0015] Furthermore, the three-dimensional porous graphene surface has a wire grid structure with a period of 10 μm, and the surface porosity reaches 12%.
[0016] Furthermore, the surface of the composite micro-nanostructure graphene has a wire grid structure with a period of 10 μm and a period of 50 μm, and the surface porosity reaches 26%.
[0017] Furthermore, the composite micro-nanostructure graphene has super hydrophobicity, and the static hydrophobic angle reaches 150°.
[0018] Furthermore, for Gram-positive Staphylococcus aureus, the antibacterial rate of the three-dimensional porous graphene reaches 85%, and the antibacterial rate of the composite micro-nanostructure graphene reaches 96%.
[0019] The present application provides a method for preparing a laser-induced composite micro-nanostructured graphene antibacterial surface. The obtained composite micro-nanostructured graphene has super hydrophobicity, and its static hydrophobic angle reaches 150°, and at the same time exhibits efficient broad-spectrum antibacterial properties. Among them, for Gram-positive Staphylococcus aureus, the antibacterial rate of the composite micro-nanostructured graphene reaches 96%, which is higher than the same type of antibacterial surface materials. In addition, since the method has the advantages of high efficiency and large-area preparation, the laser-induced graphene surface can be widely used in antibacterial and antiviral surfaces. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 A flow chart showing a method for preparing a laser-induced composite micro-nanostructured graphene antibacterial surface provided in an embodiment of the present application is shown;
[0021] Figure 2 The scanning electron microscopy images of the three-dimensional porous graphene and the composite micro-nanostructured graphene provided in the embodiments of the present application are shown;
[0022] Figure 3 The surface porosity analysis diagram of the three-dimensional porous graphene and the composite micro-nanostructured graphene provided in the embodiments of the present application is shown;
[0023] Figure 4 The Raman spectrum of the composite micro-nanostructure graphene provided in the embodiment of the present application is shown;
[0024] Figure 5 A surface hydrophobicity test diagram of the composite micro-nanostructure graphene provided in an embodiment of the present application is shown;
[0025] Figure 6 The figure shows the coated colony images of different samples exposed to the plate colony counting method for 24 hours provided in the examples of the present application. DETAILED DESCRIPTION
[0026] In order to make the purpose, technical solution and advantages of the technical solution more clear, the technical solution is further described in detail below in conjunction with specific implementation methods. It should be understood that these descriptions are only exemplary and are not intended to limit the scope of the technical solution.
[0027] Embodiment 1
[0028] Embodiment 1 of the present application provides a method for preparing a laser-induced composite micro-nanostructured graphene antibacterial surface, comprising the following steps:
[0029] S101. Prepare CO2 laser engraving machine, polyimide film, anhydrous ethanol, glass slide, and Nd:YAG laser marking machine.
[0030] As an example, the embodiments of the present application use a CO2 laser engraving machine of Voiern Laser, WER-4060, and a Nd:YAG laser marking machine of CNI laser, MK-1064.
[0031] S102, using anhydrous ethanol to ultrasonically clean the polyimide film to remove surface dirt; drying the polyimide film after ultrasonic cleaning in a vacuum oven at 60° C. to allow the polyimide film to completely adhere to the glass slide.
[0032] Wherein, the thickness of the polyimide film is 125 μm.
[0033] S103, using a CO2 laser engraving machine to graphitize the polyimide film using the local high temperature generated by the laser, to prepare a three-dimensional porous graphene with stable surface properties.
[0034] As an example, the working parameters of the CO2 laser engraving machine are set as follows: laser power is 8W, scanning speed is 200mm / s, line-by-line scanning interval is 10μm, and defocus is focal length; the size of the three-dimensional porous graphene is a square with a side length of 1cm.
[0035] In this step, the key to the preparation of three-dimensional porous graphene lies in the thermal effect of laser radiation, that is, the photothermal effect generated when laser radiation acts on the polyimide film, which forms a high-temperature area on the surface of the polyimide film. The size and temperature of the area depend on the power density and spot size of the laser spot. When the temperature exceeds the decomposition temperature of graphite oxide, it decomposes into molecules such as carbon dioxide and water, and the carbon atoms are rearranged into three-dimensional porous graphene.
[0036] Here, when the laser energy is too low, the polyimide film cannot be completely graphitized, while when the energy is too high, the surface graphene will be unstable and easy to fall off. After many experiments, the above working parameters were summarized to prepare three-dimensional porous graphene with stable surface properties.
[0037] S104, rotating the prepared three-dimensional porous graphene by 90°.
[0038] S105, using a Nd:YAG laser marking machine, using a pulsed laser to vertically scan the surface of the rotated three-dimensional porous graphene line by line to prepare a composite micro-nanostructured graphene.
[0039] The working parameters of the Nd:YAG laser marking machine are set as follows: the excitation wavelength is 1064nm, the excitation frequency is 20KHz, the laser power is 1W, the scanning speed is 200mm / s, and the line-by-line scanning interval is 50μm.
[0040] In this step, the pulsed laser scanning also removes a portion of the oxygen-containing functional groups of the three-dimensional porous graphene, plays a reducing role, and makes the pores of the prepared laser-induced graphene more uniform.
[0041] Embodiment 2
[0042] In Example 2 of the present application, a scanning electron microscope (SEM) was used to characterize the surface morphology of the prepared three-dimensional porous graphene and composite micro-nanostructured graphene to analyze their surface micro-nanostructures.
[0043] See also Figure 2 , Figure 2The following are scanning electron microscopy images of three-dimensional porous graphene and composite micro-nanostructured graphene provided in the embodiments of the present application. Figure 2 a is a scanning electron microscopy image of three-dimensional porous graphene. Figure 2 b is the enlarged surface pore image of three-dimensional porous graphene. Figure 2 c is a scanning electron microscopy image of composite micro-nanostructure graphene. Figure 2 d is the enlarged surface pore image of the composite micro-nanostructure graphene.
[0044] like Figure 2 As shown in a, the three-dimensional porous graphene presents a three-dimensional porous network structure, such as Figure 2 As shown in b, at the nanoscale, three-dimensional porous graphene is composed of graphene sheets, such as Figure 2 As shown in c, the composite micro-nanostructured graphene at the micrometer scale presents a grating-like structure, such as Figure 2 As shown in (d), the porosity of the composite micro-nanostructure graphene surface morphology is significantly increased.
[0045] After analysis, it is concluded that the three-dimensional porous graphene surface has a wire grid structure with a period of 10 μm; the composite micro-nanostructure graphene surface has a wire grid structure with a period of 10 μm and a period of 50 μm.
[0046] In addition, the present invention uses ImageJ software to analyze the porosity of the prepared three-dimensional porous graphene and composite micro-nanostructure graphene, and obtains the following: Figure 3 The surface porosity analysis diagram of three-dimensional porous graphene and composite micro-nanostructured graphene shown in the figure. In the figure, LIG represents three-dimensional porous graphene and MLIG represents composite micro-nanostructured graphene. After calculation, the surface porosity of three-dimensional porous graphene is 12.569%, and the surface porosity of composite micro-nanostructured graphene is 26.968%. It can be seen that the surface porosity of composite micro-nanostructured graphene after secondary ablation is higher than that of three-dimensional porous graphene after single ablation.
[0047] Embodiment 3
[0048] In Example 3 of the present application, Raman spectroscopy is performed on the prepared three-dimensional porous graphene and composite micro-nanostructured graphene to determine the degree of graphitization of surface carbon atoms.
[0049] In order to verify the effect of laser irradiation on the preparation of three-dimensional porous graphene and composite micro-nanostructured graphene, three samples prepared in the experiment were selected for Raman spectroscopy test, where the laser light source was 532nm. Figure 4The Raman spectra of the three-dimensional porous graphene and the composite micro-nanostructured graphene are shown in FIG. In the figure, the horizontal axis x is the Raman shift, and the vertical axis is the spectrum intensity, which represents the amount of scattered light. Similarly, LIG and MLIG are used to represent the three-dimensional porous graphene and the composite micro-nanostructured graphene, respectively. Figure 4 As shown, LIG, MLIG1 and MLIG2 have a peak at 1340 cm -1 、1570cm -1 and 2690cm -1 There are three obvious characteristic peaks at all locations, corresponding to the D, G and 2D bands of carbon materials. Among them, the appearance of the D peak is related to the defects of graphene, and the appearance of the G peak is mainly attributed to the SP 2 The vibration of carbon and the appearance of 2D peaks are related to double phonon resonance. Raman spectroscopy confirmed the composition of graphene microsheets in three-dimensional porous graphene and composite micro-nanostructured graphene.
[0050] Embodiment 4:
[0051] In Example 4 of the present application, surface hydrophobicity tests were performed on the prepared three-dimensional porous graphene and composite micro-nanostructured graphene.
[0052] By observing the surface morphology through scanning electron microscopy, it can be seen that laser ablation produces periodic micro-nano structures on the surface of three-dimensional porous graphene, increasing the porosity of the sample surface. At the same time, the presence of micro-nano structures changes the wettability of the three-dimensional porous graphene surface, making it a film with super-hydrophobic properties. Usually, three-dimensional porous graphene exhibits hydrophilicity, while composite micro-nanostructured graphene exhibits extremely strong super-hydrophobicity due to the composite micro-nanostructure on the surface.
[0053] Here, please see Figure 5 The surface hydrophobicity test diagram of the composite micro-nanostructure graphene is shown. Figure 5 As shown, the static hydrophobic angle of the composite micro-nanostructured graphene surface is measured by a contact angle meter in the embodiment of the present application, and the static hydrophobic angle is about 150°. After analysis, it can be seen that the composite micro-nanostructure of the composite micro-nanostructured graphene surface can also increase the adhesion of the droplet to its surface, showing a "petal effect" with a micro-hemispherical microstructure, resulting in a strong adhesion between its surface and the water droplet, increasing the rolling angle.
[0054] Embodiment 5
[0055] In Example 5 of the present application, the surface antibacterial properties of the prepared three-dimensional porous graphene and composite micro-nanostructured graphene were tested.
[0056] Prepare the bacterial solution required for the test:
[0057] Prepare Gram-positive Staphylococcus aureus (S. aureus, ATCC6538). After the bacteria are revived, add 9 mL of liquid culture medium to the test tube. After the cultured bacteria are shaken for a few seconds, take 1 mL and add it to the test tube and dilute it 10 times to prepare 100 μL of 10 5 CFU / mL of Staphylococcus aureus solution, and shake the test tube to mix well.
[0058] Surface antibacterial test of three-dimensional porous graphene and composite micro-nanostructure graphene:
[0059] Prepare control group samples, three-dimensional porous graphene samples and composite micro-nanostructured graphene samples;
[0060] The antibacterial ability of the sample surface is determined by dropping bacterial liquid on the sample surface and measuring the bacterial survival rate on the sample surface after 24 hours of incubation. Specifically:
[0061] The bacterial solution was added dropwise to the surface of each sample; after being cultured in an incubator for 24 hours, the bacterial solution on the sample surface was washed off; 100 μL of bacteria was taken out from the elution solution and added dropwise to the solid culture medium; the bacterial solution was evenly spread on the plate using coating beads; the colony count method was used to count the colonies, and then the percentage of colony counts of the three-dimensional porous graphene sample and the composite micro-nanostructure graphene sample was compared with that of the control group sample to calculate the antibacterial rate.
[0062] Please refer here Figure 6 The figure shows the coated colony image of different samples exposed to 24 hours by the plate colony counting method. In the figure, Control represents the control group sample. By calculating the ratio of the surface colony counts of the three-dimensional porous graphene sample and the composite micro-nanostructure graphene sample to the colony counts of the control group sample, it was found that the three-dimensional porous graphene sample and the composite micro-nanostructure graphene sample both showed strong antibacterial ability against Staphylococcus aureus. Among them, the antibacterial rate of the three-dimensional porous graphene sample after 24 hours of culture with the bacterial solution was about 85%, while the antibacterial rate of the composite micro-nanostructure graphene sample after 24 hours of culture with the bacterial solution was about 96%.
[0063] Compared with three-dimensional porous graphene, composite micro-nanostructured graphene exhibits stronger antibacterial ability. The reasons are as follows: after the composite micro-nanostructured graphene is irradiated by Nd:YAG laser for the second time, the graphene rate is increased, the number of graphene layers on the surface is reduced, and the defect rate of graphene materials is further reduced. The increase in porosity increases the contact area between bacteria and the graphene sheet structure, making it easy to destroy the cell wall and membrane structure through physical cutting, causing leakage of intracellular substances and metabolic disorders. In addition, the improvement of superhydrophobic properties reduces the contact area between bacteria and the material surface in a humid environment, making it difficult for them to survive and reproduce. At the same time, the superhydrophobic properties of the material lead to its self-cleaning ability, preventing the bacterial matrix from adhering to the surface.
[0064] The above contents are only preferred embodiments of the present invention. For ordinary technicians in this field, many changes can be made in the specific implementation methods and application scopes based on the ideas of the present technical content. As long as these changes do not deviate from the concept of the present invention, they all fall within the scope of protection of this patent.
Claims
1. A method for preparing a laser-induced composite micro-nanostructured graphene antibacterial surface, characterized in that: The method comprises: Using a CO2 laser engraving machine, the polyimide film is graphitized using the local high temperature generated by the laser to prepare three-dimensional porous graphene with stable surface properties; The prepared three-dimensional porous graphene was rotated 90°; Using a Nd:YAG laser marking machine, a pulsed laser is used to scan the surface of the rotated three-dimensional porous graphene line by line in the vertical direction to prepare composite micro-nanostructured graphene.
2. The method according to claim 1, characterized in that Before using the CO2 laser engraving machine for graphitization, the method further includes: The polyimide film was ultrasonically cleaned using anhydrous ethanol to remove surface dirt; The polyimide film after ultrasonic cleaning was dried in a vacuum oven at 60° C. to allow the polyimide film to completely adhere to the glass slide.
3. The method according to claim 1, characterized in that The thickness of the polyimide film is 125 μm.
4. The method according to claim 1, characterized in that The working parameters of the Nd:YAG laser marking machine are set as follows: The excitation wavelength is 1064 nm, the excitation frequency is 20 KHz, the laser power is 1 W, the scanning speed is 200 mm / s, and the scanning interval is 50 μm.
5. The method according to claim 1, characterized in that The three-dimensional porous graphene surface has a wire grid structure with a period of 10 μm, and the surface porosity reaches 12%.
6. The method according to claim 1, characterized in that The composite micro-nanostructure graphene surface has a wire grid structure with a period of 10 μm and a period of 50 μm, and the surface porosity reaches 26%.
7. The method according to claim 1, characterized in that The composite micro-nanostructure graphene has super hydrophobicity, and the static hydrophobic angle reaches 150°.
8. The method according to claim 1, characterized in that For Gram-positive Staphylococcus aureus, the antibacterial rate of the three-dimensional porous graphene reaches 85%, and the antibacterial rate of the composite micro-nanostructure graphene reaches 96%.